Association of mental demands in the workplace with cognitive function in older adults at increased risk for dementia - Zülke AE; Luppa M; Röhr S; Weißenborn M; Bauer A; Samos F-AZ; Kühne F; Zöllinger I; Döhring J; Brettschneider C; Oey A; Czock D; et al. (BioMed Central Ltd, 2021)
Objectives Growing evidence suggests a protective effect of high mental demands at work on cognitive function in later life. However, evidence on corresponding associations in older adults at increased risk for dementia is currently lacking. This study investigates the association between mental demands at work and cognitive functioning in the population of the AgeWell.de-trial. Methods Cross-sectional investigation of the association between global cognitive functioning (Montreal Cognitive Assessment) and mental demands at work in older individuals at increased risk for dementia (Cardiovascular Risk Factors, Aging, and Incidence of Dementia (CAIDE)score ≥ 9; n = 941, age: 60–77 years). Occupational information was matched to Occupational Information Network (O*NET)-descriptors. Associations between cognitive function and O*NET-indices executive, verbal and novelty were investigated using generalized linear models. Results Higher values of index verbal (b = .69, p = .002) were associated with better cognitive function when adjusting for covariates. No association was observed for indices executive (b = .37, p = .062) and novelty (b = .45, p = .119). Higher education, younger age, and employment were linked to better cognitive function, while preexisting medical conditions did not change the associations. Higher levels of depressive symptomatology were associated with worse cognitive function. Conclusions Higher levels of verbal demands at work were associated with better cognitive function for older adults with increased dementia risk. This suggests an advantage for older persons in jobs with high mental demands even after retirement and despite prevalent risk factors. Longitudinal studies are warranted to confirm these results and evaluate the potential of workplaces to prevent cognitive decline through increased mental demands.
Keywords: Cognition; Cognitive decline; Dementia; Mental demands; Occupation; Risk factors; Workplace; Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Cross-Sectional Studies; Dementia; Humans; Workplace